Oral manifestations of type 2 diabetes mellitus of Bhopal city: an observational prospective study - Saxena, Vijay; Saxena, Divya; Desai, Ami; Shrivastava, Saurabh (International Journal of Medical Research and Review, 2017)
Introduction: Type 2 diabetes mellitus involves a variety of dysfunctions bringing about a few delicate tissue variations from the norm in the oral cavity. These incorporate gingivitis periodontitis, salivary dysfunction, taste dysfunction, oral fungal and bacterial infections, geographic tongue, benign migratory glossitis, fissured tongue, traumatic ulcer, lichen planus, angular cheilitis, delayed mucosal healing, dental root caries, tooth loss, mucosal neurosensory disorders, and oral mucosal lesions. Aim and objectives: This study aims to determine the frequency of different oral manifestations in patients of Type 2 Diabetes Mellitus of Bhopal city which will expand the consciousness of oral signs of diabetes mellitus subsequently helping in speeding up the examination regarding this matter. Methodology: This descriptive study was carried out at the Department of Medicine, People’s Hospital, hitech division, Bhopal from March 2016 to January 2017. 200 patients satisfying the inclusion criteria (diagnosed cases of type 2 diabetes mellitus of > 35 years of age) were included in the study. 84 (42%) were female and 116(58%) were male patients. Result: The frequency of different oral manifestations seen in female diabetic patients in descending order were; gingivitis (49%), periodontitis (36.7%), dental root caries (20%), taste dysfunction (8%), burning mouth syndrome (8%), xerostomia (31%), recurrent apthous stomatitis (11%) and oral candidiasis (2%) and in male diabetic patients in descending order were; gingivitis (41%), periodontitis (29%), dental root caries (18%), taste dysfunction (9%), burning mouth syndrome (3%), xerostomia (31%), recurrent apthous stomatitis (5%) and oral candidiasis (3%). Conclusion: It was inferred that diabetic patients are more inclined to get oral complications so health education, timely diagnosis and effective treatment should be carried out to prevent these complications.